The development of learning modul of colloid system integrated with project based learning (PjBL) system to increase the result of students’ learning - Sri Wartika; Zainuddin Muchtar; Wesly Hutabarat (Pascasarjana Universitas Negeri Medan, 2021)
This research aims to develop learning material in the form of colloid learning system module integrated with PjBL model in accordance with curriculum 2013 and to find out the increasing of students learning result after using learning module of colloid system integrated with Project Based Learning (PjBL) system. The type of the study is development research and experiment. It examines how the module of Integrated with Project Based Learning (PjBL) integrated with PjBL model is organized based on curriculum 2013 and the experiment is managed by analyzing the using of the module in senior high school. The study was carried out to the students of 9th grade of SMA Negeri 1 Sunggal and SMA Swasta Muhammadiyah 18 Sunggal school year of 2018/2019 in second semester. The data are examined by using independent sample of T-test by using SPSS 23 program. The result shows that colloid system module integrated with PjBL developed model is valid and appropriate to be used based on BSNP.The score of the students who are taught by with the module has increased in average about 82.80 (high) with a pretest score of 31.80 (low), the score of the students who are taught by using textbooks increase to 77.60 (middle) with a pretest score of 32.40 (low).Keywords: Module, Colloid, Project based learning